MODEL DEVELOPMENT OF CREATIVE DRAWING TRAINING MANAGEMENT WITH THE TOPIC OF CONSERVATION FOR KINDERGARTEN TEACHERS IN SEMARANG (Universitas Negeri Semarang, 2014)
Training is an effective way to professionally improve teachers’ human resource. The purpose of this training was to prepare professional kindergarten teachers to make creative drawing to children golden age. Teachers have significant roles in their